Digitally measuring solar ultraviolet radiation in outdoor workers: A study protocol for establishing the use of electronic personal dosimeters in Portugal - Paulo, Marília Silva; Symanzik, Cara; Maia, Melanie R.; Lapão, Luís Velez; Carvalho, Fernanda; Conneman, Sven; Dias, Jorge Barroso; Gobba, Fabriziomaria; John, Swen Malte; Loney, Tom; Pinho, Cristina; Rodrigues, Ana; et al. (Frontiers in Public Health, 2023)
Introduction: The rising incidence of skin cancer over the years has made it a significant public and occupational health issue. However, skin cancer is highly preventable, mainly through reduced exposure to solar ultraviolet radiation (UVR), which can be achieved by a variety of individual and collective protective measures and interventions. The relative risk associated with different patterns of exposure to solar UVR differs for the subtypes of keratinocyte cancers (KC). Specifically, whether the exposure is intermittent or continuous, and occurs in an occupational or leisure/recreational setting. The main aim of the study using this protocol is to contribute to raising public and policy awareness on solar UVR-inflicted occupational skin cancers in Lisbon. This will be achieved by performing direct measurements of the solar UVR dose received by outdoor workers using a digital platform. Results will likely contribute to further understanding the risk estimates for keratinocyte cancer estimations in this population. Methods: A prospective observational study will be conducted in Lisbon, Portugal. Personal electronic dosimeters (GENESIS-UV system) integrated with a digital platform will be used to assess occupational solar UVR doses of gardeners, masons, and gravediggers of the municipality of Lisbon. Two hundred and ten outdoor workers will be selected to wear the dosimeter for one month each, between April and October during their daily working hours. A digital web-based platform that offers private access to information through dashboard visualization will provide information for the outdoor workers and facilitate communication with the participants. Discussion: The expected results of the overall proposal comprise the occupational solar UVR doses, expressed in Standard Erythemal Dose (SEDs) per day of outdoor work for seven months. Study data will provide outdoor workers with information on their personal solar UVR exposure during their working hours and an estimate of their risk of developing skin cancer. It is expected that the occupational solar UVR doses of the outdoor workers in Portugal will be above the threshold of 1 to 1.33 SED/day, due to the latitude of Lisbon and the nature of the occupations. The results prospectively should flow into the design of adequate prevention campaigns for skin cancer.